Örgüt Kültürü Algısı ve Örgütsel Çift Yönlülük İlişkisi: Örgütsel Düzeyde Bilgi Paylaşımının Aracılık Etkisi (The Relationship Between The Perception of Organisational Culture and Organizational Ambidexterity: Moderating Effects of Information Sharing On The Organisational Level) - Mine AFACAN FINDIKLI; İbrahim PINAR (Yönetim ve Ekonomi, 2014)
The main purpose of this study is to investigate whether there is a significant effect of the organisational culture percieved by supervisors to the organizational ambidexterity. The results of the studies realised on enterprises showed that cultural tightness and cultural looseness perception influence the organizational ambidexterity. However, a meaningful relationship between the perception of organisational culture (tightness/ looseness culture) with the information sharing on the organizational level could not be detected. Besides, it isn’t found that the information sharing on the organisational level has a significant effect of the organizational ambidexterity. Therefore, it isn’t found that the information sharing on the organizational level has a moderating effect on the relationship between the perception of organizational culture and the organisational ambidexterity.